Ammonium Chloride: An Efficient and Environmentally benign Catalyst for Knoevenagel Condensation of Carbonyl and Active Methylene Compounds - Tasqeeruddin, S.; I. Asiri, Yahya; Mujahid Alam, M. (Asian Journal of Chemistry, 2020)
In the present study, a rapid, simple and an efficient procedure for the Knoevenagel condensation of various carbonyl and active methylene compounds in ethanol at a moderate temperature in the presence of a catalytic amount of an efficient, environmentally benign and inexpensive ammonium chloride is reported. Simple reaction procedure, economic and ecofriendly catalyst, mild reaction conditions and good to excellent yield of the products are the characteristic features of this study. The non-extractive workup/purification, economic and environmentally benign catalyst make this operationally straightforward procedure affordable for large scale.